Vital signs role and significance in detecting early cardiac events - Alzahrani, Meshal S.; Albishi, Amal H.; Alfaifi, Abeer E.; Alzahrani, Ahmed M.; Aldoosary, Reem I.; Alshabeeb, Sajedah Y.; Alammar, Ayat A.; Alalrashidi, Bandar M.; Zoqeei, Eman M.; Kofiyah, Omar A. (International Journal Of Community Medicine And Public Health, 2023)
Cardiovascular diseases continue to be a contributor to mortality highlighting the significance of intervention. Nurses are often the first healthcare professionals to assess patients and their ability to identify symptoms and deviations in signs is essential for early detection of cardiac distress. Many individuals encounter symptoms such as discomfort in the chest, trouble with breathing, irregularities, heartbeat and increased fatigue. These symptoms can be signs of events. Nurses’ attentiveness in monitoring these symptoms and vital signs enables response and lifesaving interventions. Furthermore, advancements in healthcare technology like automated monitoring systems and telehealth platforms enhance nurse’s ability to detect events by allowing real time data collection and remote monitoring. This review explores the role that nurses play in detecting events early on with a specific focus, on monitoring vital signs like blood pressure and heart rate. The comprehensive management of events encompasses accurate diagnosis, evidence-based treatment, patient education and modification of risk factors. The expertise and constant vigilance of nurses significantly contribute to improving care and enhancing patient outcomes. As healthcare technology continues to advance nurses role in detecting events becomes even more crucial solidifying their indispensable position, in promoting heart health.